Automated MRI Brain Tumor Classification and Cancer Detection Using Support Vector Machine - Rahman, M. A (International Journal of Computer Sciences and Engineering, 2025)
this research paper proposes an automated and intelligent classification technique of Magnetic Resonance Imaging (MRI) brain images which is extremely important for medical analysis and interpretation. ECG, CT-scan and MRI images are important ways to diagnose brain diseases efficiently. An abnormal growth of cells without any purposes is called a tumor. Sometimes doctors can tell if a tumor is cancer or isn’t using MRI. MRI also used to find the signs that cancer may have spread from its starting part to another part of the body. Radiologist or physician analyze tumor manually by visual inspection which is a conventional method. This may lead to error in classification while a large number of MRIs are to be analyzed. Brain cancer is the leading cause of death among people which is caused from malignant brain tumor. A benign tumor is one that does not invade nearby tissue but a malignant tumor does. The chances of survival can be increased if the tumor can be detected at its early stage. In this paper a novel method to classify brain tumors as benign (non-cancerous) or malignant (cancerous) is presented. MRI brain image database was used for training and testing. Images were filtered, skull-masked and segmented. The proposed method employed wavelet transform to extract features from several images. Principle component analysis (PCA) was applied to reduce dimensionality of features. Gray Level Co-occurrence Matrix (GLCM) based Features were selected and submitted to a kernel support vector machine (KSVM). To generalize KSVM, k-fold stratified cross validation was applied. Features were extracted from MRI images named gray scale, symmetrical and texture features. The main goal of this paper is to offer an excellent result of MRI brain tumor classification and cancer detection using SVM. Our proposed system achieved classification accuracy of 96% for RBF kernel